(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The necessity of implementing enough adaptation strategies to maintain ecosystem sustainability Droughts, along with other hydroclimatic disturbances, are on the rise, as demonstrated by recent studies. Climate change is predicted to cause events to occur more frequently and with greater intensity due to global warming. Droughts hurt crop yield and vegetation growth, which increases the threats to a nation like India’s food security, which must feed more than a billion people. Given the growing threats posed by climate change, it is imperative to analyze the relationship between extreme climate conditions and terrestrial ecosystem productivity, also known as Net Primary Productivity or NPP. The study was conducted across 10 types of vegetation and 25 river basins in India. Additionally, the potential of the terrestrial environments to withstand severe disruptions were assessed every year as well as during the monsoon and non-monsoon seasons. Only five river basins’ terrestrial ecosystems were found to be resistant to extremely harsh weather, according to the results, which indicated that 15 of the 25 river basins were in danger. Furthermore, it was discovered that eight out of ten types of vegetation cover were unable to withstand extreme environmental conditions and that at least 50% of the area covered by four out of ten vegetation cover types faced a significant risk of a sharp decline in NPP. Our findings make it easier to determine which areas of the nation are most vulnerable to climate change and ecosystem management, and they emphasize